Acute postinfectious glomerulonephritis with a large number of crescents caused by Mycoplasma pneumoniae - Xinghua Chen; Wanwen Xu; Juan Du; Huiming Wang (Wolters Kluwer Medknow Publications, 2015)
Mycoplasma pneumoniae-induced acute postinfectious glomerulonephritis has various pathological changes and relatively poor prognosis. It often occurs in children, barely in adults. Currently, no clear treatment guidelines have been established for its treatment using glucocorticoid and immunosuppressive. In this study, we report an adult who admitted to our hospital due to fever and gross hematuria. The patient presented with nephritic syndrome and renal failure and confirmed to have M. pneumoniae infection by serum detection and acute postinfectious glomerulonephritis with a large number of crescents by renal biopsy. He was given glucocorticoid, immunosuppressive agent combined with hemodialysis as well as other supportive treatment. Three months later, his renal function became normal, urine protein level decreased to 0.4 g/24 h, and the C3 complement increased to normal level. In conclusion, glucocorticoid and immunosuppressive treatment should be given to patients with M. pneumoniae-infection induced glomerulonephritis after confirmed to have a large number of crescents by renal biopsy and the treatment could improve the prognosis.